Electrolyte, electrochemical device and electronic device
By adding compounds shown in Formula I to the electrolyte solution of lithium-ion batteries, a dense solid electrolyte membrane is formed, which solves the problem of degradation in cycling performance and high-temperature storage performance of lithium-ion batteries under high voltage, and achieves better battery performance and service life.
Patent Information
- Application Number
- CN202280003035.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-29
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-03-29
AI Technical Summary
When used at high voltages, the cycling and high-temperature storage performance are significantly reduced, resulting in rapid attenuation and expansion of capacity.
An electrolyte containing a specific compound is used, which includes a compound represented by Formula I, for forming a dense solid electrolyte membrane at the positive electrode oxidation and forming a solid electrolyte membrane at the interface of the negative electrode, through which the side reactions and gas production are reduced and cell performance is improved.
It effectively improves the circulation performance and high-temperature storage performance of lithium-ion batteries and extends the service life of the battery.
Smart Images

Figure CN115298875B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and in particular to an electrolyte, an electrochemical device and an electronic device. Background Art
[0002] Electrochemical devices (e.g., lithium-ion batteries) have high energy density, wide operating temperature range, and long cycle life, and have become the main energy source for current mobile electronic devices. With the development of lightweight electrochemical devices, it is necessary to further develop electrochemical devices with high capacity density. At present, taking lithium-ion batteries as an example, when the charging cut-off voltage of lithium-ion batteries is increased from 4.45V to 4.55V, its effective capacity is significantly improved, but with it, the performance of lithium-ion batteries is significantly reduced, especially the cycle performance and high-temperature storage performance; under high voltage, the oxidation activity of the positive electrode active material is high, and the electrolyte is accelerated to oxidize and decompose on the surface of the positive electrode material, producing a large amount of gas, and the oxidation products are continuously deposited on the surface of the positive electrode, resulting in the continuous growth of the battery internal resistance and thickness, causing the capacity of the lithium-ion battery to decay rapidly and the expansion to increase significantly.
[0003] As an important component of an electrochemical device, the electrolyte has a great influence on the cycle performance and storage performance of the electrochemical device. Therefore, there is an urgent need to provide an electrolyte to improve the cycle performance and high-temperature storage performance of the electrochemical device. Summary of the invention
[0004] In view of the problems existing in the background technology, the purpose of the present application is to provide an electrolyte, an electrochemical device and an electronic device.
[0005] In order to achieve the above-mentioned object, the present application provides an electrolyte, which comprises a compound represented by formula I,
[0006]
[0007] Wherein X is selected from Li + 、Na + , K + or Rb + .
[0008] In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound represented by formula I is 0.005%-1.5%.
[0009] In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound represented by formula I is 0.01%-1%.
[0010] In some embodiments, the electrolyte further comprises fluoroethylene carbonate; in some embodiments, based on the mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is 1%-10%.
[0011] In some embodiments, the compound represented by Formula I includes at least one of the following compounds:
[0012]
[0013] In some embodiments, the electrolyte further comprises a nitrile compound, wherein the nitrile compound comprises a compound represented by Formula II:
[0014]
[0015] Among them, R 1 is selected from substituted or unsubstituted C 1-10 Alkyl, substituted or unsubstituted C 1-10 Alkenyl, substituted or unsubstituted C 1-10 Alkynyl, substituted or unsubstituted C 1-10 Alkoxy, substituted or unsubstituted C 1-10 One of the heterocyclic groups of , wherein, when substituted, the substituent is halogen;
[0016] R 2 , R 3 , R 4 are independently selected from a hydrogen atom or a cyano group;
[0017] Based on the mass of the electrolyte, the mass percentage of the compound represented by formula II is 0.1% to 5%.
[0018] In some embodiments, the nitrile compound comprises at least one of the following compounds:
[0019]
[0020] In some embodiments, the electrolyte further comprises lithium difluorophosphate; in some embodiments, based on the mass of the electrolyte, the mass percentage of the lithium difluorophosphate is 0.005% to 1%.
[0021] In some embodiments, the present application provides an electrochemical device, including a positive electrode sheet, a negative electrode sheet, a separator, and the above-mentioned electrolyte.
[0022] In some embodiments, the present application also provides an electronic device, which includes the above-mentioned electrochemical device.
[0023] This application has at least the following beneficial effects:
[0024] The electrolyte in the present application can effectively improve the cycle performance and high-temperature storage performance of the electrochemical device. DETAILED DESCRIPTION
[0025] It will be understood that the disclosed embodiments are merely examples of the present application, which can be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as the basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present application in various ways.
[0026] In the description of the present application, unless otherwise clearly specified and limited, the terms "Formula I", "Formula II" and the like are used for illustrative purposes only and are not to be understood as indicating or implying relative importance and mutual relationship.
[0027] (Electrolyte)
[0028] In some embodiments, the electrolyte comprises a compound of formula I,
[0029]
[0030] Wherein X is selected from Li + 、Na + , K + or Rb + .
[0031] The compound shown in Formula I can be oxidized at the positive electrode to form a dense solid electrolyte (CEI) film, which can improve the stability of the positive electrode, reduce the side reaction of the electrolyte at the positive electrode interface, reduce gas production, and improve the room temperature cycle performance and high temperature storage performance of the electrochemical device.
[0032] In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound of formula I is 0.005%-1.5%. In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound of formula I is 0.005%-1%. In some embodiments, based on the mass of the electrolyte, the content of the compound of formula I in the electrolyte may be 0.005%, 0.015%, 0.05%, 0.2%, 0.3%, 0.4%, 0.5%, 1.0%, 1.5% or any range therebetween.
[0033] In some embodiments, the electrolyte further comprises fluoroethylene carbonate; based on the mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is 1%-10%. In some embodiments, based on the mass of the electrolyte, the content of the fluoroethylene carbonate in the electrolyte can be 1.0%, 2.5%, 5.0%, 7.5%, 10% or any range therebetween.
[0034] Further adding fluoroethylene carbonate (FEC) to the electrolyte containing the compound shown in Formula I can further improve the cycle performance of the electrochemical device, because FEC can be reduced at the negative electrode to form a solid electrolyte (SEI) film, and continuously repair the negative electrode surface during the cycle of the electrochemical device, thereby inhibiting the consumption of solvents and other film-forming additives in the electrolyte during the cycle; at the same time, the CEI film formed by the compound shown in Formula I at the positive electrode interface can inhibit the etching of the positive electrode by FEC and stabilize the positive electrode interface. The two can jointly improve the room temperature cycle performance of the electrochemical device through a synergistic effect. However, when the amount of FEC added is too high, the impedance of the negative electrode interface will increase, and it may also cause side reactions at the electrode interface, resulting in increased gas production, which will affect the high temperature storage performance of the electrochemical device.
[0035] In some embodiments, the compound represented by Formula I includes at least one of the following compounds:
[0036]
[0037] In some embodiments, the electrolyte further comprises a nitrile compound, wherein the nitrile compound comprises a compound represented by Formula II:
[0038]
[0039] Among them, R 1 is selected from substituted or unsubstituted C 1-10 Alkyl, substituted or unsubstituted C 1-10 Alkenyl, substituted or unsubstituted C 1-10 Alkynyl, substituted or unsubstituted C 1-10 Alkoxy, substituted or unsubstituted C 1-10 One of the heterocyclic groups of , wherein when substituted, the substituent is halogen; R 2 , R 3 , R 4 Each of the compounds of formula II is independently selected from a hydrogen atom or a cyano group. Based on the mass of the electrolyte, the mass percentage of the compound of formula II is 0.1% to 5%. In some embodiments, based on the mass of the electrolyte, the content of the compound of formula II in the electrolyte can be 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3%, 3.5%, 4.0%, 4.5%, 5.0% or any range therebetween.
[0040] A compound represented by formula II is further added to an electrolyte containing the compound represented by formula I or an electrolyte added with fluorinated ethylene carbonate (FEC). Since the compound represented by formula II contains a cyano substituent, it can be adsorbed on the cathode surface to form a protective film. The formed protective film can effectively block the contact between the solvent molecules in the electrolyte and the positive electrode surface, significantly reduce the oxidation of the electrolyte by the positive electrode surface of the electrochemical device during the cycle, and further reduce the side reaction between the positive electrode and the electrolyte, thereby effectively improving the room temperature cycle performance of the electrochemical device and improving its high temperature storage performance.
[0041] In some embodiments, the nitrile compound comprises at least one of the following compounds:
[0042]
[0043] In some embodiments, the electrolyte further comprises lithium difluorophosphate; based on the mass of the electrolyte, the mass percentage of the lithium difluorophosphate is 0.01% to 1%. In some embodiments, based on the mass of the electrolyte, the mass percentage of the lithium difluorophosphate in the electrolyte can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 1.0% or any range therebetween.
[0044] When lithium difluorophosphate is further added to an electrolyte containing the compound represented by formula I, an electrolyte added with fluoroethylene carbonate (FEC), or an electrolyte containing the compound represented by formula II, since lithium difluorophosphate can also participate in the formation of an SEI film at the negative electrode interface and the formed SEI film is further modified, the ionic conductivity and stability of the SEI film formed at the negative electrode interface can be increased, the side reaction between the negative electrode and the electrolyte can be inhibited, the gas production can be reduced, and the transmission impedance of active metal ions at the negative electrode interface can be reduced, thereby further improving the cycle performance of the electrochemical device and enhancing its high-temperature storage performance.
[0045] In some embodiments, the electrolyte further includes a lithium salt and a non-aqueous organic solvent.
[0046] In some embodiments, the lithium salt includes or is selected from at least one of an organic lithium salt and an inorganic lithium salt.
[0047] In some embodiments, the lithium salt includes or is selected from lithium hexafluorophosphate (LiPF 6 ), lithium bis(oxalatoborate) (LiB(C 2 O 4 ) 2 , LiBOB), lithium difluorooxalatoborate (LiBF 2 (C 2 O 4 ), LiDFOB), lithium tetrafluoroborate (LiBF 4), lithium hexafluoroantimonate (LiSbF 6 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium perfluorobutanesulfonate (LiC 4 F 9 SO 3 ), lithium perchlorate (LiClO 4 ), lithium aluminate (LiAlO 2 ), lithium tetrachloroaluminate (LiAlCl 4 ), Lithium Bissulfonyl Imide (LiN(C x F 2x+1 SO 2 )(C y F 2y+1 SO 2 ), wherein x and y are natural numbers), at least one of lithium chloride (LiCl) or lithium fluoride (LiF).
[0048] In some embodiments, based on the mass of the electrolyte, the mass percentage of the lithium salt is 10% to 15%, preferably 12% to 15%.
[0049] In some embodiments, the non-aqueous organic solvent may include a carbonate solvent, a carboxylate solvent, an ether solvent, a sulfone solvent, other organic solvents, or a combination thereof.
[0050] In some embodiments, carbonate solvents may include but are not limited to at least one of linear carbonate compounds or cyclic carbonate compounds. The above-mentioned linear carbonate compounds may include but are not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or ethyl methyl carbonate. The above-mentioned cyclic carbonate may include but are not limited to at least one of ethylene carbonate (also referred to as ethylene carbonate), vinylene carbonate, propylene carbonate, butylene carbonate (or vinyl ethylene carbonate).
[0051] In some embodiments, the carboxylate solvent may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran.
[0052] In some embodiments, the ether solvent includes at least one of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,4-dioxane, and 1,3-dioxane.
[0053] In some embodiments, the sulfone solvent includes at least one of sulfolane, dimethyl sulfoxide, and methyl sulfolane.
[0054] In some embodiments, the other organic solvent includes at least one of 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate ester.
[0055] In the present application, the organic solvent in the electrolyte may be a single non-aqueous organic solvent or a mixture of multiple non-aqueous organic solvents. When a mixed solvent is used, the mixing ratio may be controlled according to the required electrochemical device performance.
[0056] (Electrochemical Device)
[0057] Next, the electrochemical device of the present application will be described.
[0058] The electrochemical device of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In some embodiments, the electrochemical device may include, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0059] In some embodiments, the electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator, and the electrolyte described above in the present application.
[0060] The preparation process of the electrochemical device is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a wound structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device; or stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0061] [Positive electrode]
[0062] In some embodiments, the positive electrode sheet includes a current collector and a positive active material layer disposed on the current collector. In the present application, there is no particular restriction on the positive current collector, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to aluminum foil, aluminum alloy foil or composite current collector, etc. In the present application, there is no particular restriction on the thickness of the positive current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 8μm to 12μm. In the present application, the positive electrode material layer can be disposed on one surface or two surfaces along the thickness direction of the positive current collector. It should be noted that the "surface" here can be the entire area of the positive current collector or a partial area of the positive current collector. There is no particular restriction in the present application, as long as the purpose of the present application can be achieved.
[0063] In some embodiments, the positive electrode active material includes a compound that reversibly intercalates and deintercalates lithium ions. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the above positive electrode active material may be doped and / or coated. In some embodiments, the coating element for the coating layer may include K, Na, Ca, Mg, B, Al, Co, Si, V, Ga, Sn, Zr, or a mixture thereof.
[0064] In some embodiments, the positive electrode active material layer further includes a binder and a conductive agent. In some embodiments, the conductive agent in the positive electrode active material layer may include at least one of conductive carbon black, acetylene black, Ketjen black, lamellar graphite, graphene, carbon nanotubes or carbon fibers. In some embodiments, the binder in the positive electrode active material layer may include polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, styrene-acrylate copolymer, styrene-butadiene copolymer, polyamide, sodium carboxymethyl cellulose, polyvinyl acetate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, polyhexafluoropropylene or polymethyl methacrylate. Optionally, the positive electrode may also include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The present application does not particularly limit the composition of the conductive layer, and may be a conductive layer commonly used in the art.
[0065] [Negative electrode]
[0066] In some embodiments, the negative electrode sheet includes a negative electrode active material layer on the current collector. The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include but is not limited to copper foil, copper alloy foil, aluminum foil, stainless steel foil, titanium foil, nickel foam, copper foam or composite current collector, etc. In the present application, there is no particular restriction on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. In the present application, the negative electrode material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of the negative electrode current collector or a partial area of the negative electrode current collector. The present application has no particular restrictions, as long as the purpose of the present application can be achieved.
[0067] The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a material that can reversibly embed / de-embed lithium ions. In some embodiments, the material that can reversibly embed / de-embed lithium ions includes but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO 2 , spinel-structured lithiated TiO 2 -Li 4 Ti 5 O 12 Or at least one of Li-Al alloy.
[0068] In some embodiments, the negative electrode active material layer may further include a conductive agent and / or a binder. The conductive agent in the negative electrode active material layer may include at least one of carbon black, acetylene black, Ketjen black, lamellar graphite, graphene, carbon nanotubes, carbon fibers, or carbon nanowires. In some embodiments, the binder in the negative electrode active material layer may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylic acid salt, polyacrylate, polyvinyl pyrrolidone, polyaniline, polyimide, polyamide-imide, polysiloxane, styrene-butadiene rubber, epoxy resin, polyester resin, polyurethane resin, or polyfluorene. Optionally, the negative electrode plate may also include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application does not particularly limit the composition of the conductive layer, which may be a conductive layer commonly used in the art, and the conductive layer may include but is not limited to the above-mentioned conductive agent and the above-mentioned binder.
[0069] The negative electrode can be prepared by a preparation method known in the art. For example, the negative electrode can be obtained by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition, and coating the active material composition on a current collector.
[0070] [Isolation film]
[0071] In some embodiments, the electrochemical device of the present application is provided with a separator between the positive electrode and the negative electrode to prevent short circuit.
[0072] In some embodiments, the isolation membrane includes a substrate layer and a surface treatment layer. The material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide or aramid. In some embodiments, the polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. The isolation membrane of the present application may have a porous structure, and the size of the pore size is not particularly limited, as long as the purpose of the present application can be achieved. For example, the size of the pore size can be 0.01μm to 1μm. In the present application, the thickness of the isolation membrane is not particularly limited, as long as the purpose of the present application can be achieved. For example, the thickness can be 5μm to 500μm.
[0073] In some embodiments, the isolation membrane surface may also be provided with a surface treatment layer. The surface treatment layer is provided on at least one surface of the substrate of the isolation membrane, and the surface treatment layer includes at least one of an inorganic layer or a polymer layer. In some embodiments, the inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from aluminum oxide (Al 2 O 3 ), silicon oxide (SiO 2 ), magnesium oxide (MgO), titanium oxide (TiO 2 ), hafnium dioxide (HfO 2 ), tin oxide (SnO 2 ), cerium dioxide (CeO 2 ), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO 2 ), yttrium oxide (Y 2 O 3 ), at least one of silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate.
[0074] In some embodiments, the binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.
[0075] The porous layer on the surface of the isolation membrane can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the electrode. In some embodiments, the polymer material in the polymer layer is selected from at least one of polyacrylonitrile, polyacrylic acid salt, polyamide, polyvinylidene fluoride, and polyvinyl pyrrolidone.
[0076] [case]
[0077] The shell is used to encapsulate the electrode assembly. In some embodiments, the shell can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.; or it can be a soft package, such as a bag-type soft package, and the material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0078] In some embodiments, the positive electrode sheet, the negative electrode sheet and the isolation membrane can be made into an electrode assembly through a winding process or a lamination process. The electrode assembly is placed in a shell, injected with the electrolyte, and an electrochemical device can be obtained after vacuum packaging, standing, forming, shaping, and capacity separation.
[0079] [Electronic devices]
[0080] The present application also provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electrochemical device provided by the present application has good cycle performance and high temperature storage performance, so that the electronic device provided by the present application has a long service life.
[0081] The electronic device of the present application is any electronic device, such as but not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor. It is noted that the electrochemical device of the present application is applicable to energy storage power stations, marine vehicles, and air vehicles in addition to the electronic devices listed above. Air vehicles include air vehicles within the atmosphere and air vehicles outside the atmosphere.
[0082] [test]
[0083] The present application is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.
[0084] In the following examples and comparative examples, the reagents, materials and instruments used can be obtained commercially or synthetically unless otherwise specified.
[0085] The lithium ion batteries in Examples 1-49 and Comparative Example 1 were prepared according to the following method:
[0086] (1) Preparation of electrolyte
[0087] In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate, diethyl carbonate, and propylene carbonate were mixed in a mass ratio of 2:7:1, and then the fully dried lithium salt LiPF 6 Dissolved in the above solvent to obtain an electrolyte, wherein LiPF 6 The mass percentage is 12.5wt%. A certain mass of the compound represented by formula I, FEC, the compound represented by formula II or lithium difluorophosphate is added to the electrolyte prepared above.
[0088] (2) Preparation of positive electrode sheet:
[0089] The positive electrode active material is lithium cobalt oxide (LiCoO 2 ), conductive agent acetylene black, binder polyvinylidene fluoride (PVDF) are dissolved in an appropriate amount of N-methylpyrrolidone (NMP) solvent in a weight ratio of 96:2:2 and stirred thoroughly to form a uniform positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, the aluminum foil is dried at 85°C, and then compacted, cut and slit by a roller press, and dried at 85°C under vacuum conditions for 4 hours to obtain the positive electrode.
[0090] (3) Preparation of negative electrode sheet:
[0091] The negative electrode active material graphite, the binder styrene butadiene rubber (SBR), the conductive agent acetylene black, and the thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water in a weight ratio of 95:2:2:1 and fully stirred and mixed to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, the copper foil is dried at 85°C, and then cold pressed, cut and slit; and dried at 120°C under vacuum conditions for 12 hours to obtain a negative electrode.
[0092] (4) Preparation of isolation membrane:
[0093] 7 μm thick PE porous polymer film.
[0094] (5) Preparation of lithium-ion batteries:
[0095] The positive electrode, the separator, and the negative electrode are stacked in order, so that the separator is placed between the positive electrode and the negative electrode to play an isolating role, and they are wound to obtain a bare battery cell. After welding the pole ears, the bare battery cell is packaged with an aluminum-plastic film, and the water content is kept below a certain value at 80°C. The prepared electrolyte is injected, and after vacuum packaging, a soft-pack lithium-ion battery (thickness 3.3 mm, width 39 mm, length 96 mm) is obtained after standing, forming, and shaping, thereby completing the preparation of the lithium-ion battery.
[0096] Next, the performance test process and test results of lithium-ion batteries are described.
[0097] (1) 25℃ cycle test
[0098] Place the lithium-ion battery in a 25℃ constant temperature box and leave it to stand until the lithium-ion battery reaches a constant temperature; charge it at 0.5C constant current to 4.55V, charge it at constant voltage to a current of 0.025C; discharge it at 1C to 3.0V, and the capacity at this step is the initial capacity C 0 Repeat the above steps until the cycle is 100 times, and record the capacity of 100 cycles as C 1 The capacity retention rate of lithium-ion batteries after 100 cycles at 25°C is calculated according to the following formula:
[0099] Capacity retention rate = C 1 / C 0 ×100%
[0100] (2) 60℃ high temperature storage test
[0101] The lithium-ion battery was discharged at 0.5C to 3.0V at 25°C, then charged at 0.2C constant current to 4.55V, and charged at 4.55V to a current of 0.025C. The thickness of the lithium-ion battery was measured and recorded with a micrometer, and recorded as H. 1 ; Store at 60℃ for 4 days, then use a micrometer to measure and record the thickness of the lithium-ion battery, which is recorded as H 2 .
[0102] The thickness expansion rate of lithium-ion battery stored at 60°C is calculated according to the following formula: 2 -H 1 ) / H 1 ×100%.
[0103] The electrolytes and lithium-ion batteries of the examples and comparative examples were prepared according to the above method and tested.
[0104] Table 1 Parameters of Comparative Example 1 and Examples 1-20
[0105]
[0106]
[0107] It can be seen from Examples 1-9 and Comparative Example 1 that adding a specific amount of the compound represented by Formula I to the electrolyte of a lithium-ion battery can significantly improve the normal temperature cycle while improving the high temperature storage performance of the battery. The reason is that the compound represented by Formula I is preferentially oxidized at the positive electrode to form a dense CEI film, which prevents damage to the surface structure of the positive electrode, improves the stability of the positive electrode, reduces the side reaction of the electrolyte at the positive electrode interface, and reduces gas production, thereby improving the cycle and high temperature storage performance of the battery.
[0108] It can be seen from Examples 1-9 and Examples 10-20 that by further adding fluoroethylene carbonate (FEC) to the electrolyte containing the compound represented by Formula I, the cycle performance of the battery is further improved. This is because FEC is reduced at the negative electrode to form an SEI film, and continuously repairs the negative electrode surface during the cycle process, thereby inhibiting the consumption of solvents and other film-forming additives during the cycle process. The CEI film formed by the compound represented by Formula I can inhibit the etching of the positive electrode by FEC, thereby improving the room temperature cycle performance of the lithium-ion battery through a synergistic effect.
[0109] Table 2 Parameters of Example 2, Example 12 and Examples 21-33
[0110]
[0111] It can be seen from the examples in Table 2 that by further adding the compound represented by Formula II to the electrolyte containing the compound represented by Formula I or the electrolyte added with fluoroethylene carbonate (FEC), the molecules containing cyano groups can effectively block the contact between the solvent molecules and the positive electrode surface when adsorbed on the cathode surface, thereby greatly reducing the oxidation of the electrolyte by the positive electrode surface of the charged lithium-ion battery, thereby improving the room temperature cycle performance and the high temperature storage performance.
[0112] Table 3 Parameters of Example 2, Example 12 and Examples 34-49
[0113]
[0114]
[0115] It can be seen from the examples in Table 3 that lithium difluorophosphate is further added to the electrolyte containing the compound represented by Formula I or the electrolyte added with fluoroethylene carbonate (FEC) or the electrolyte containing the compound represented by Formula II. Since lithium difluorophosphate further modifies the formed solid electrolyte membrane, the ionic conductivity and stability of the negative electrode graphite SEI membrane are increased, the side reaction between the electrode and the electrolyte is suppressed, the cycle performance of the battery is further improved, and the high temperature storage performance is enhanced.
[0116] The above example data show that adding the compound of formula I or a combination of the compound of formula I and one or more other additives to the electrolyte can significantly improve the cycle performance and high temperature storage performance of the lithium-ion battery.
[0117] The above disclosed features are not intended to limit the scope of implementation of the present disclosure. Therefore, all equivalent changes made to the contents described in the claims of the present disclosure should be included in the scope of the claims of the present disclosure.
Claims
1. An electrolyte, wherein comprising at least one of the compounds represented by formula I, Wherein X is selected from Li + Or Na + ; Based on the mass of the electrolyte, the mass percentage of the compound represented by formula I is 0.02%-0.5%; The electrolyte also includes fluoroethylene carbonate; based on the mass of the electrolyte, the mass percentage of the fluoroethylene carbonate is 1%-10%.
2. The electrolyte according to claim 1, wherein The electrolyte further comprises a nitrile compound, wherein the nitrile compound comprises a compound represented by formula II: Wherein, R1 is selected from substituted or unsubstituted C 1-10 Alkyl, substituted or unsubstituted C 1-10 Alkenyl, substituted or unsubstituted C 1-10 Alkynyl, substituted or unsubstituted C 1-10 Alkoxy, substituted or unsubstituted C 1-10 One of the heterocyclic groups of , wherein, when substituted, the substituent is halogen; R2, R3, and R4 are independently selected from a hydrogen atom or a cyano group; Based on the mass of the electrolyte, the mass percentage of the compound represented by formula II is 0.1% to 5%.
3. The electrolyte according to claim 2, wherein The nitrile compound comprises at least one of the following compounds:
4. The electrolyte according to claim 1, wherein The electrolyte also includes lithium difluorophosphate; Based on the mass of the electrolyte, the mass percentage of the lithium difluorophosphate is 0.005% to 1%.
5. An electrochemical device comprising a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte according to any one of claims 1 to 4.
6. An electronic device comprising the electrochemical device according to claim 5.
Citation Information
Patent Citations
Nonaqueous electrolyte, nonaqueous secondary battery, cell pack, and hybrid system
CN110352527A
Electrolyte additive, non-aqueous electrolyte and lithium ion battery
CN112510260A
Electrolyte solution, electrochemical device, and electronic device
CN112803068A
Non-aqueous electrolyte and secondary battery thereof
CN113363581A